IMPLEMENTASI LOCATION-BASED SERVICE PADA APLIKASI TIAS BERBASIS ANDROID UNTUK PEMBELAJARAN MAHASISWA - Ramadhan, Wahyu; Fitrah Satrya Fajar Kusumah; Safaruddin Hidayat Al-Ikhsan (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study examines the application of Location-Based Service (LBS) in the Android-based TIAS application developed to facilitate student learning activities. This study aims to assess how the use of Location-Based Services (LBS) can improve the effectiveness and accuracy of the student attendance system in a university environment. In its implementation, LBS allows the TIAS application to verify the physical location of students when they take attendance so as to prevent attendance made outside the predetermined location. This research adopts both qualitative and quantitative approaches to examine various aspects of LBS implementation, including technological accuracy, impact on data privacy and security, and user experience.